2010
DOI: 10.1007/s10230-010-0124-2
|View full text |Cite
|
Sign up to set email alerts
|

Alkalinity Generation in a Novel Multi-stage High-strength Acid Mine Drainage and Municipal Wastewater Passive Co-treatment System

Abstract: Passive co-treatment of high-strength acid mine drainage (AMD) and municipal wastewater (MWW) was examined in a laboratory-scale, four-stage continuous flow reactor system with a total residence time of 6.6 d. Synthetic AMD of pH 2.60 and an acidity of 1,870 mg/L (as CaCO 3 ) was mixed at a 1:2 ratio with raw MWW (pH 7.67, 288 mg/L alkalinity (as CaCO 3 ), and 265 mg/L BOD 5 ) from the City of Norman, Oklahoma and introduced into the system. Alkalinity generated by limestone dissolution and bacterial SO 4 2-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Techniques like the co-treatment of municipal wastewater (with biosolids as byproducts) and AMD has recently gained popularity following its introduction by Roetman [39], when it was proposed to remove pathogens in sewage [40]. Results from studies to date have shown the removal of metals, certain nutrients, increases in pH and alkalinity, and overall water/leachates quality improvements [41][42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Techniques like the co-treatment of municipal wastewater (with biosolids as byproducts) and AMD has recently gained popularity following its introduction by Roetman [39], when it was proposed to remove pathogens in sewage [40]. Results from studies to date have shown the removal of metals, certain nutrients, increases in pH and alkalinity, and overall water/leachates quality improvements [41][42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the challenge is to find a suitable inexpensive and sustainable carbon source for adequate reduction of sulphates (Santamaria et al, 2014). The co-treatment of AMD and municipal wastewater has become a treatment option of interest as the simultaneous treatment of municipal wastewater and AMD allows a reduction in treatment costs (Strosnider et al, 2011a;Strosnider et al, 2011b;Strosnider et al, 2013). A 1:1 ratio of AMD and sewage also showed a significant decrease in acidity, organic matter, nutrients, iron and manganese concentrations, and complete removal of pathogens (Neto et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Domestic wastewater has a significant environmental impact due to its insufficient treatment in developing countries (Gadgil, 1998;Strosnider et al, 2011a). The passive co-treatment of AMD and domestic wastewater can meet the requirements of both treatment processes as the effluent of each consists of elements that can be used by the other (Strosnider et al, 2011b). Domestic wastewater is readily available and is therefore a convenient and cost-effective carbon source for potential treatment of AMD (Gadgil, 1998;Strosnider et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of biofilms has been described at AMD sites (Denef et al, 2011;Smucker and Vis, 2011) and may therefore play a potential role in AMD treatment. Domestic wastewater has a significant environmental impact due to its insufficient treatment in developing countries (Gadgil, 1998;Strosnider et al, 2011a). The passive co-treatment of AMD and domestic wastewater can meet the requirements of both treatment processes as the effluent of each consists of elements that can be used by the other (Strosnider et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation